1987
DOI: 10.1002/jor.1100050114
|View full text |Cite
|
Sign up to set email alerts
|

Porous hydroxyapatite as a bone graft substitute in diaphyseal defects: A histometric study

Abstract: Porous hydroxyapatite (IP200), formed by conversion of the Poritidae porites exoskeleton, has pores averaging 230 microns and pore interconnections averaging 190 microns in diameter. In the distal radial diaphyses of 14 dogs, bilateral 7.5 X 20 mm cortical windows were created and fitted with 5 X 7.5 X 20 mm blocks of IP200 implants and iliac autografts. Both implanted and contralateral grafted radius specimens were retrieved at 3, 6, 12, 24, and 48 months. Unstained undecalcified sections were examined by mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(73 citation statements)
references
References 14 publications
2
66
1
1
Order By: Relevance
“…However, bone formation in the ProOsteon 200 group was signi cantly greater than in the allograft group in zone 2, indicating that ProOsteon 200 is a good osteoconductor (Table 2). ProOsteon is a slow resorbing bone substitute (Shimazaki and Mooney 1985, Holmes et al 1987, el Deeb and Holmes 1989, Martin et al 1993). Accordingly, we found no signi cant resorption of HA granules after 3 weeks (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…However, bone formation in the ProOsteon 200 group was signi cantly greater than in the allograft group in zone 2, indicating that ProOsteon 200 is a good osteoconductor (Table 2). ProOsteon is a slow resorbing bone substitute (Shimazaki and Mooney 1985, Holmes et al 1987, el Deeb and Holmes 1989, Martin et al 1993). Accordingly, we found no signi cant resorption of HA granules after 3 weeks (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Porosity is an important factor for the biological fixation of bioceramics to living bone, 5) while the pore size and morphology of the scaffolds affects tissue ingrowth to the implanted biomaterials. 6) Furthermore, porosity plays an important role in the mechanical fixation between biomaterials and hard living tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite ceramics (HA) materials have been used as a substitute for bone grafting because the crystalline phase of natural bone is similar to that of HA (16,17), while porous calcium hydroxyapatite ceramics (CHA) materials have been utilized in orthopedic and craniofacial surgery procedures since the 1980s (18). However, few studies have reported cases in which conventional CHA became fully filled by newly formed bone, which may be due to its structure and limited connectivity between pores (19).…”
Section: Discussionmentioning
confidence: 99%